(untitled) (Imaginations: Journal of Cross-Cultural Image Studies, 2016)
Abstract | Photography has an important place, both contemporary and historical, in shaping visions, understandings, and experiences of the Canadian West. The varied uses of early photographs of the West, circulated in a moment of national consciousness brought on by Confederation, shaped the collective Canadian imagination. Contemporary artists and scholars continue to be influenced by many of the same ideas that emerged in this early moment of Canadian history, when both country and medium developed alongside one another. Themes of exploration, identity, colonialism, settlement, tourism, natural resource, industry, and ecology find as much resonance in historical photographs in archival and museological collections as they do in contemporary photography and critical discourse. This essay bridges historical themes and archival pieces with the images of contemporary photographers working in western Canada today, whose photographs are featured in this issue. This essay sets the historical framework that endures in themes that contemporary photographers explore and also links the artists featured in this issue into a shared visual history. Résumé | La photographie a une place importante, contemporaine et historique, dans les visions de mise en forme, dans l’élaboration de visions, compréhensions, et expériences de l’Ouest canadien. Les utilisations variées des premières photographies de l’Ouest, circulé dans un moment de la conscience nationale provoquée par la Confédération, ont façonné l’imaginaire collectif canadien. Artistes contemporains sont encore influencés par un grand nombre des mêmes idées qui émergent en ce moment au début de l’histoire canadienne, à un moment que le pays et la photographie développer ensemble. Thèmes de l’exploration, l’identité, le colonialisme, le règlement, le tourisme, les ressources naturelles, l’industrie, et l’écologie sont résonnant dans les photographies historiques maintenant continues dans des collections d’archives et de musées comme dans les photographies contemporaines et l’écriture de celui-ci. Cet essai relie des thèmes historiques et œuvres d’archives avec le travail de photographes contemporains travaillant dans l’Ouest du Canada aujourd’hui, et qui est présentée dans ce journal. Cet essai se développe l’histoire qui persiste dans les thèmes que les photographes contemporains explorent dans leur travail, et servir comme un lien entre les artistes présentés dans ce journal dans une histoire visuelle commune.